Agricultural Livelihoods and Climate Change: Employing the Livelihood Vulnerability Index in Bluefields, Jamaica - Kevin Lee Fath; Taniya Jayani Koswatta; Gary Wingenbach (Journal of International Agricultural and Extension Education, 2018)
The purpose of this quantitative study was to examine agricultural livelihood vulnerability to climate change in Bluefields, Westmoreland, Jamaica based on the Livelihoods Vulnerability Index (LVI). Random sampling was used to select participants. Personal interviews were conducted with farmers using an instrument consisting of LVI components representing livelihood strategies, natural and physical assets, socio-demographic profile, social networks, water issues, food issues, natural disasters, and climate variability. LVI data were aggregated using an indexing approach to create scores for comparison across vulnerability components. The results showed farmers in Bluefields had the most amount of vulnerability in social networks and water issues. Low numbers of farmers owned their land, had contact with extension services, or used irrigation. Most farmers reported having problems with access to seeds and planting material, depended on their farms for food, and experienced frequent crop failure. Development organizations and local change agents should target the areas of greatest vulnerability illuminated by this study. Vulnerability and its contributing factors of exposure, sensitivity, and adaptive capacity, should be reassessed with the LVI and other methods to monitor changes in Bluefields over time. Implications for extension educators to assist subsistence farmers in understanding better the effects of climate change are noted
Keywords: Agricultural livelihood vulnerabilities; climate change; Jamaica